Different visual exploration of tool-related gestures in left hemisphere brain damaged patients is associated with poor gestural imitation. (May 2015) - Vanbellingen, Tim; Schumacher, Rahel; Eggenberger, Noëmi; Hopfner, Simone; Cazzoli, Dario; Preisig, Basil C.; Bertschi, Manuel; Nyffeler, Thomas; Gutbrod, Klemens; Bassetti, Claudio L.; Bohlhalter, Stephan; Müri, René M.
Abstract: According to the direct matching hypothesis, perceived movements automatically activate existing motor components through matching of the perceived gesture and its execution. The aim of the present study was to test the direct matching hypothesis by assessing whether visual exploration behavior correlate with deficits in gestural imitation in left hemisphere damaged (LHD) patients. Eighteen LHD patients and twenty healthy control subjects took part in the study. Gesture imitation performance was measured by the test for upper limb apraxia (TULIA). Visual exploration behavior was measured by an infrared eye-tracking system. Short videos including forty gestures (20 meaningless and 20 communicative gestures) were presented. Cumulative fixation duration was measured in different regions of interest (ROIs), namely the face, the gesturing hand, the body, and the surrounding environment. Compared to healthy subjects, patients fixated significantly less the ROIs comprising the face and the gesturing hand during the exploration of emblematic and tool-related gestures. Moreover, visual exploration of tool-related gestures significantly correlated with tool-related imitation as measured by TULIA in LHD patients. Patients and controls did not differ in the visual exploration of meaningless gestures, and no significant relationships were found between visual exploration behavior and the imitation of emblematic and meaningless gestures in TULIA. The present study thus suggests that altered visual exploration may lead to disturbed imitation of tool related gestures, however not of emblematic and meaningless gestures. Consequently, our findings partially support the direct matching hypothesis. Highlights: A direct link between the perception and imitation of tool-related gestures Left hemisphere brain damaged patients show an altered visual exploration behavior Gesture perception tasks may be integrated in gestural training